Efficacy and Safety of Photobiomodulation Therapy for Motor Symptoms in Parkinson’s Disease: A Systematic Review and Meta-Analysis - Joao Mariano; Eneidy Piña Mojica; Andrés Soto-Rodríguez; Anna Carolyna Gianlorenço; Kevin Pacheco-Barrios; Felipe Fregni (Brain Sciences, 2026)
Background: Parkinson’s disease (PD) is a progressive neurodegenerative disorder causing disabling motor dysfunction and substantial socioeconomic burden. Photobiomodulation (PBM), a noninvasive red/near-infrared light therapy, has shown preclinical promise, but its clinical efficacy and safety in PD remain uncertain. Objectives: To systematically evaluate the efficacy and safety of PBM on motor outcomes in PD. Methods: This PRISMA-compliant systematic review was prospectively registered in PROSPERO (CRD420261411269). Databases were searched through May 2026. Randomized and non-randomized trials in adults with PD were included. Two reviewers independently screened studies, extracted data, and assessed risk of bias (RoB 2.0; ROBINS-I). Where data permitted, random-effects meta-analyses used mean difference (MD) with REML estimation and Hartung–Knapp–Sidik–Jonkman confidence intervals. Results: Eight trials (n = 279) were included, exhibiting substantial heterogeneity in wavelength, device type, stimulation sites, and dosimetry. PBM was safe and well tolerated, with only minor adverse effects. Meta-analysis of four RCTs found no significant effect on MDS-UPDRS-III (MD = −1.37 points, 95% CI: −5.55 to 2.80; I2 = 20.6%) or TUG (MD = −0.52 s, 95% CI: −5.03 to 3.99; I2 = 55.1%). An exploratory TMWT meta-analysis (k = 2) yielded MD = −0.65 s (95% CI: −1.78 to 0.49; I2 = 0.0%), with direction consistently favoring PBM. Individual effect sizes ranged from negligible (d = 0.03–0.06) to small-to-moderate (d = 0.41). Conclusions: PBM appears safe, feasible, and acceptable in PD, but current evidence does not support clinically meaningful motor benefits. Heterogeneous protocols, small samples, and absent target-engagement biomarkers limit definitive interpretation. Well-powered standardized trials with mechanistic endpoints are needed.